(untitled) (Pain medicine, 2025)
BACKGROUND: sacral erecter spinae plane block is a relatively new and safe interfascial plane block for paediatric urogenital surgeries. We aimed at comparing the intraoperative and postoperative analgesic efficacy of Bupivacaine alone and Bupivacaine plus Dexamethasone in ultrasonography guided single shot sacral erecter spinae plane block for urogenital surgeries in paediatric patients under general anaesthesia. METHODS: 30 patients, ASA 1 / 2, 12 months – 12 years undergoing urogenital surgeries were randomly divided into 2 groups. Under general anaesthesia, in prone position, with linear ultrasound probe placed longitudinally in the midline; 25 G, 90 mm spinal needle was advanced craniocaudally until its tip reached the 4th sacral crest and prepared drug was injected Group A received 1ml/kg of 0.25% Bupivacaine with 2ml saline Group B received 1 ml/kg of 0.25% Bupivacaine with 0.2mg/kg Dexamethasone in saline to make total volume of 2 ml. RESULTS: All patients remained haemodynamically stable intraoperatively in both groups with comparable duration of analgesia postoperatively. Also, the difference in mean FLACC R score upto 24 hours postoperatively was not significant between the two groups and no side effects were reported. CONCLUSION: The addition of Dexamethasone to Bupivacaine in ultrasonography guided single shot sacral erecter spinae plane block for urogenital surgeries in paediatric patients under general anaesthesia neither modified the analgesic efficacy of Bupivacaine intraoperatively nor did it significantly prolong the duration of analgesia postoperatively.